Students as leaders in supporting campus well‐being: Peer‐to‐peer health promotion in higher education. (26th April 2021) - Reis, Arianne; Mortimer, Taylor; Rutherford, Erin; Sperandei, Sandro; Saheb, Rowena
Abstract: Issue addressed: This study aimed to analyse the relationship between peer‐delivered health promotion programmes and student well‐being and to expand the limited body of research examining peer‐to‐peer mental health promotion as experienced by student leaders. Methods: The study was cross‐sectional and focused on the experience of participants of a Sydney‐based University Mental Health Day event, including student leaders, student participants, university staff and industry partners. It adopted a mixed‐method approach to data collection, including a quantitative and a qualitative phase. Results: Results from the quantitative phase demonstrate the benefits of peer‐delivered health promotion programmes to students who receive the event. Results from the qualitative phase of the study provide a deeper insight into the delivery of the event, from both a student leader perspective, and also from the perspective of other stakeholders, who worked closely with student leaders. Two main themes emerged from the qualitative material and are explored in detail: enabling leadership and creating a sense of purpose. Conclusion: The study concludes that, while there is mounting evidence of the benefits of student‐led mental health programmes for both leaders and their peers, more research needs to be carried out to better understand how to optimise these experiences and unlock their full potential with reference to student mental health. So what?: With the ongoing pressure on university student services to support student well‐being not being met with appropriate resourcing, peer‐to‐peer programmes, like the Mental Health and Well‐being Student Ambassador Programme, have a real opportunity to make strides in supporting and promoting student mental health.